Analisis Resouce Based View di PT Garuda Maintenance Facility (GMF) AeroAsia Studi Analisis pada Unit Base Maintenance - , Risang Megandaru; , Dr. Budi Santoso, M.Bus ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The company that owns and uses resources and capabilities efficiently have a greater opportunity to operate economically and satisfy customers better. Thus, to be able to maintain superior performance in an industry, then a company should be protected by the factors that can make it difficult to imitate by competitors, or as Rumelt calls Isolating Mechanism. Resource Based View is to study these factors, and basing thoughts on the idea that every company basically has a fundamental difference because it has a unique set of resources. This study aims to determine the resources and capabilities of GMF AeroAsia in airframe maintenance business that has the potential through an analysis of the value chain and also to analyze the implementation of resourcebased view of GMF AeroAsia in airframe maintenance business in order to achieve sustainable competitive advantage by using VRIO analysis (Valuable, Rarity, Imitability, Organization) Framework. The results showed that almost all of the resources and capabilities of GMF AeroAsiaâs source of competitive advantage is only competitive parity. This is due to the fact that resources and capabilities is also owned by its competitors, such as ST Aero, HAECO, SIAEC and MAS. Meanwhile, only manhours rate of GMF AeroAsia are relatively cheaper when compared to competitors who have temporary characteristics of sustained competitive advantage.